A new species of Argostemma (Rubiaceae) with free stamens in star-shaped corolla from the Philippines - Hsu, Hao Wei C.; Aranas, Denmarc R.; Alejandro, Grecebio Jonathan D.; Liede-Schumann, Sigrid (Phytotaxa, 2020)
Argostemma separatum, a new species with free stamens in star-shaped corolla from Mt. Halcon Oriental Mindoro, Philippines is here described and compared with Argostemma diversifolium, the only species of the genus with this type of flower. This species is distinct from A. diversifolium by its indumentum on stem, leaf blades and calyx, smaller leaf blades, fewer flowered inflorescences, shape of stipule and calyx, red tips on corolla lobes, and color of anthers. Based on the recent IUCN categories, the conservation status of A. separatum is Data Deficient (DD) since it was only collected at the type locality.